Understanding community family medicine preceptors’ involvement in educational scholarship: perceptions, influencing factors and promising areas for action - Ward, Michael; Schultz, Karen; Grady, Colleen; Roberts, Lynn Maria (Canadian Medical Education Journal, 2021)
Background: Residency training is increasingly occurring in community settings. The opportunity for community-based scholarship is untapped and substantial. We explored Community Family Medicine Preceptors’ understanding of Educational Scholarship (ES), looked at barriers and enablers to ES, and identified opportunities to promote the growth of ES in this setting. Methods: We conducted semi-structured interviews with fifteen purposively chosen community-based Family Medicine preceptors in a distributed Canadian family medicine program. Results: Community Family Medicine Preceptors strongly self-identify as clinical teachers. They are not well acquainted with the definition of ES, but recognize themselves as scholars. Community Family Medicine Preceptors recognize ES has significant value to themselves, their patients, communities, and learners. Most Community Family Medicine Preceptors were interested and willing to invest in ES, but lack of time and scarcity of primary care research experience were seen as barriers. Research process support and a connection to the academic center were considered enablers. Opportunities to promote the growth of ES include recognition that there are fundamental differences between community and academic sites, the development of a mentorship program, and a process to encourage engagement. Conclusions: Community Family Medicine Preceptors identify foremost as clinician teachers. They are engaged in and recognize the value of ES to their professional community at large and to their patients and learners. There is a growing commitment to the development of ES in the community